Postępowanie właściwe dla stwierdzenia niezgodności z prawem niewydania decyzji (art. 4171 §3 k.c.) - Matan, Andrzej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The article is a devoted to one of the special cases of liability for damage caused by unlawful omission in the exercise of a public authority involving the failure to give a decision where the obligation to issue it provides rule of law.
Keywords: decision; damage; proper conduct; omission; liability for damage